2021
DOI: 10.2147/jmdh.s326967
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Body Aspiration in Egyptian Children Clinical, Radiological and Bronchoscopic Findings

Abstract: Purpose: Foreign body aspiration (FBA) is a frequent cause of childhood morbidity and mortality. Diagnosis of FBA is challenging in the absence of a witnessed aspiration event. The aim of this study was to determine the accuracy of presenting symptoms as well as physical and radiologic findings as predictors of FBA in children. Thus, indications for bronchoscopy could be determined in such cases. Methods: This retrospective cohort study was conducted in the ENT department, Kafrelsheikh University Hospital. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The aspiration of FB is almost exclusive to children, as shown by our results and the literature consulted [6,[8][9][10][11][12]. At these ages, FB aspiration accidents often occur because children eat while jumping on swings, jumping ropes, and playing other games.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The aspiration of FB is almost exclusive to children, as shown by our results and the literature consulted [6,[8][9][10][11][12]. At these ages, FB aspiration accidents often occur because children eat while jumping on swings, jumping ropes, and playing other games.…”
Section: Discussionmentioning
confidence: 57%
“…The bronchial location is the most common among all airway locations [8,11,12,14,15], followed by the trachea and larynx. According to the literature [16], the setting of the FB in one of the bronchi depends on the oldness of the patient and the physical position of the patient at the time of aspiration (vertical position), knowing that the angle that is formed between the trachea and the two bronchi is similar until the age of 15, we can find a FB in either bronchus (if the patient is in an upright position) with the same probability.…”
Section: Discussionmentioning
confidence: 99%
“…Radiological imaging can help detect these complications and guide appropriate management. In a study by Reyad et al (12) , the authors reported that X-ray of the left and right bronchi was useful in detecting complications of inhaled foreign bodies, including atelectasis, pneumonia, and lung abscess.…”
Section: Discussionmentioning
confidence: 99%
“…Foreign Body Aspiration (FBA) is a critical pediatric problem that requires timely diagnosis and prompt management. It leads to either complete or partial airway obstruction and causes significant morbidity and or mortality (Reyad et al, 2021& Alshehri et al, 2019. It has been estimated that the vast majority 80% of pediatrics' foreign body aspiration episodes occur in children younger than 3 years with a peak prevalence between 1 and 2 years of age, during the toddler stage of development (Rose & Dubensky, 2019).…”
Section: Introductionmentioning
confidence: 99%